Micronized milo and urea in high-hay growing rations for beef heifers - Bolsen, K.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Twenty-four individually fed heifers were used to evaluate four combinations of micronized or dry-rolled milo and soybean meal or urea supplements in prairie hay growing rations. Feeding 5 lbs. of micronized milo produced 23% faster and 18% more efficient gains than feeding 5 lbs. of dry-rolled milo. Heifers fed micronized milo + urea tended to gain faster and more efficiently than heifers fed dry-rolled milo + soybean meal.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Micronized milo; Urea; Rations; Heifers